Usability of Bank Capital Buffers : The Role of Market Expectations - Abad, Jose (IMF Working Papers; Working Paper ;, 2022)
Following the COVID shock, supervisors encouraged banks to use capital buffers to support the recovery. However, banks have been reluctant to do so. Provided the market expects a bank to rebuild its buffers, any draw-down will open up a capital shortfall that will weigh on its share price. Therefore, a bank will only decide to use its buffers if the value creation from a larger loan book offsets the costs associated with a capital shortfall. Using market expectations, we calibrate a framework for assessing the usability of buffers. Our results suggest that the cases in which the use of buffers make economic sense are rare in practice.